Changes in Vascularization of Human Breast Cancer Xenografts Responding to Antiestrogen Therapy - Kristensen, Claus A (Stockton Press, 1999)
To elucidate the previously suggested vascular effect(s) of antiestrogen therapy, we studied the effect of estrogen withdrawal and tamoxifen on 1) vascular resistance, 2) glucose and oxygen consumption, and 3) vascular density in a perfused breast cancer line (ZR75-1). Furthermore, we examined ZR75-1 tumors by functional CT-scanning (fCT) to determine changes in parameters related to tumor capillary transfer constants and vascular volume fraction in response to antiestrogenic manipulations. The vascular resistance decreased significantly from 42.7 to 20.8 mmHg x min x g x ml(-1) (P< .03) on day 9 after estrogen withdrawal, but not after 9 days of tamoxifen treatment. The estrogen-depleted tumors were significantly smaller than controls on day 9. There was no difference in nutrient consumption or vascular density in any of the experimental groups compared to controls. fCT showed an increase (P < .03) in vascular volume fraction during tumor growth, and this parameter was significantly lower after estrogen withdrawal when compared to controls (P < .05). Vascular resistance correlated with tumor size (R = 0.7, P < .0001), indicating that vascular resistance increases during tumor growth. The changes in vascular parameters after estrogen withdrawal indicate a vascular remodeling effect. This inhibition of vascular development by hormone deprivation may have important implications for future planning of multimodal treatment regimens.